2021
DOI: 10.3390/microorganisms9030642
|View full text |Cite
|
Sign up to set email alerts
|

High Efficacy of Saliva in Detecting SARS-CoV-2 by RT-PCR in Adults and Children

Abstract: Rising demands for repetitive SARS-CoV-2 screens and mass testing necessitate additional test strategies. Saliva may serve as an alternative to nasopharyngeal swab (NPS) as its collection is simple, non-invasive and amenable for mass- and home testing, but its rigorous validation, particularly in children, is missing. We conducted a large-scale head-to-head comparison of SARS-CoV-2 detection by RT-PCR in saliva and NPS of 1270 adults and children reporting to outpatient test centers and an emergency unit. In t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
3
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 48 publications
6
56
3
4
Order By: Relevance
“…In fact, it avoids the discomfort of the nasopharyngeal swab, protects health workers from exposure to the virus and overcomes the problem of the lack of nasopharyngeal swabs. In addition to rapid salivary antigen test which identifies the viral Spike protein based on the lateral flow assay (132), there is salivary RT-PCR test (133,134). The detection of SARS-CoV-2 by RT-PCR in saliva showed a positive percent agreement of 92.5% compared to analysis in nasopharyngeal swabs, underlining that the saliva is a generally reliable specimen for the detection of SARS-CoV-2, with particular advantages for testing children (134).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it avoids the discomfort of the nasopharyngeal swab, protects health workers from exposure to the virus and overcomes the problem of the lack of nasopharyngeal swabs. In addition to rapid salivary antigen test which identifies the viral Spike protein based on the lateral flow assay (132), there is salivary RT-PCR test (133,134). The detection of SARS-CoV-2 by RT-PCR in saliva showed a positive percent agreement of 92.5% compared to analysis in nasopharyngeal swabs, underlining that the saliva is a generally reliable specimen for the detection of SARS-CoV-2, with particular advantages for testing children (134).…”
Section: Diagnosismentioning
confidence: 99%
“…In addition to rapid salivary antigen test which identifies the viral Spike protein based on the lateral flow assay (132), there is salivary RT-PCR test (133,134). The detection of SARS-CoV-2 by RT-PCR in saliva showed a positive percent agreement of 92.5% compared to analysis in nasopharyngeal swabs, underlining that the saliva is a generally reliable specimen for the detection of SARS-CoV-2, with particular advantages for testing children (134). Salivary RT-PCR testing could be a valuable tool in mass screening strategies, especially for controlling the pandemic during the reopening period, for providing variant monitoring, and for routine testing of children as well.…”
Section: Diagnosismentioning
confidence: 99%
“…Therefore, controlled evaluations in large, well-defined cohorts are critical. To this end, we recently conducted a large-scale head-to-head comparison of SARS-CoV-2 detection by RT-PCR in NPS and saliva of adults and children in a test center setting [ 21 ]. We demonstrated that saliva is a reliable alternative specimen for the detection of SARS-CoV-2 by RT-PCR with particular advantages for testing children.…”
Section: Introductionmentioning
confidence: 99%
“…While immunological tests describe the antibody response to infection, the direct identification of the virus in respiratory or saliva specimens can be carried out by antigenic tests or by amplification of its genome through RT-qPCR or ddPCR. The latter approaches, currently called “molecular tests”, are indicated as the gold standard in defining positive cases when the viral load is low [ 8 , 9 , 10 , 11 , 12 ]. Nevertheless, individual screening of large asymptomatic cohorts by RNA extraction and RT-qPCR can be expensive and wasteful when pathogens are present in the population at low carriage rates.…”
Section: Introductionmentioning
confidence: 99%